HANDLING AND STABILITY ANALYSIS OF AN AUTOMATED VEHICLE WITH INTEGRATED FOUR-WHEEL INDEPENDENT STEERING (4WIS) - Changoski, Vasko; Gjurkov, Igor; Janushevska, Vase (Faculty of Engineering, University of Kragujevac, 2024)
The latest revisions of the UN and the European Union regulations regarding the steering system allow implementation of novel technologies in automated vehicles. Four-wheel independent steering (4WIS) system represents an upgrade of the steer-by-wire concept that enhances the capabilities of the steering system. The primary focus of this research is to enhance vehicle handling and stability performance by integration of four-wheel independent steering (4WIS) and vehicle stability control (VSC) system in an automated vehicle. A virtual vehicle equipped with 4WIS and VSC is created in ADAMS/Car. The proposed control algorithms are implemented in MATLAB/Simulink and their effect is tested in co-simulation environment. As a control method, Sliding Mode Control (SMC) is used to improve vehicle handling while maintaining vehicle stability under different driving conditions. The proposed concept is evaluated through different open-loop and path following manoeuvres to thoroughly assess its performance.
Keywords: Four-wheel independent steering (4WIS), steer-by-wire, co-simulation, vehicle handling, vehicle stability